Configurations atmosphériques de vastes échelles spatiales et variabilité des surcotes dans le Golfe du Lion - Albin Ullmann; Vincent Moron (Cybergeo, 2007)
This paper is based on the analysis of sea-surge variations in the Gulf of Lions. A sea surge is defined as the difference between the observed sea level and the astronomical tide. It corresponds to the sea-level height only forced by meteorological conditions. The main goal of our study is to analyze broad-scale climatic conditions linked to the regional and local-scale sea-surges formation in the Golfe du Lion. Around this gulf, daily variations of sea-surge heights are mostly linked with the sea-level pressure variation over the Bay of Biscay. Surge peaks almost always occurred during “Greenland Above” and “Blocking” Weather Regimes. These weather regimes are potentially associated with local meteorological conditions enable to lead to a surge peak.